Addressing Nanomaterial Immunosafety by Evaluating Innate Immunity across Living Species. Issue 21 (4th May 2020) - Boraschi, Diana; Alijagic, Andi; Auguste, Manon; Barbero, Francesco; Ferrari, Eleonora; Hernadi, Szabolcs; Mayall, Craig; Michelini, Sara; Navarro Pacheco, Natividad I.; Prinelli, Alessandra; Swart, Elmer; Swartzwelter, Benjamin J.; et al.
Abstract: The interaction of a living organism with external foreign agents is a central issue for its survival and adaptation to the environment. Nanosafety should be considered within this perspective, and it should be examined that how different organisms interact with engineered nanomaterials (NM) by either mounting a defensive response or by physiologically adapting to them. Herein, the interaction of NM with one of the major biological systems deputed to recognition of and response to foreign challenges, i.e., the immune system, is specifically addressed. The main focus is innate immunity, the only type of immunity in plants, invertebrates, and lower vertebrates, and that coexists with adaptive immunity in higher vertebrates. Because of their presence in the majority of eukaryotic living organisms, innate immune responses can be viewed in a comparative context. In the majority of cases, the interaction of NM with living organisms results in innate immune reactions that eliminate the possible danger with mechanisms that do not lead to damage. While in some cases such interaction may lead to pathological consequences, in some other cases beneficial effects can be identified. Abstract : When confronted with engineered nanomaterials, living organisms from plants to human beings rely on their immune defensive system for keeping at large any possible danger. Many defensive responses are common across evolution. In many instances, the interaction leads to successful elimination, while in a minority of cases, the reaction may lead to pathological consequences.